Mortalidade materna no Estado do Maranhão - Guarda, Olivani Izabel Domanski (2017)
Maternal mortality is a serious public health problem in Brazil, especially in the Northeast region and most significantly in the State of Maranhão. This study aimed to characterize maternal mortality in Maranhão between 2010 and 2014. This is a descriptive, retrospective study of all maternal deaths declared in the SIM between 2010 and 2014 of women residing in the State, by Regional Health. It was based In data collected in SIM, SINASC and in the Deputy Secretary of Health Surveillance of the Government of the State of Maranhão. Sociodemographic variables focused on age, race / color, schooling and marital status. The variables related to the deaths focused on the moment of death, place of occurrence and type of obstetric cause. There were 516 maternal deaths and 472 were submitted to spatial analysis. The following results were observed: MMR in the State presented very high and high values, according to WHO classification, in most of the Health Region in the years studied. The highest spatial density of deaths occurred in the Regional of São Luis. Predominant direct obstetric causes in brown women, between 20 and 29 years, with no partner and with little schooling, which portrays the expression of social inequity and evidences the need to improve prenatal care, delivery and puerperium in the State of Maranhão